Screencast-O-Matic to Support EFL Teaching and Learning Amidst the COVID-19 Pandemic - Yustinus Calvin Gai Mali; Made Hery Santosa (Beyond Words, 2021)
The COVID-19 situation causes a sudden and unexpected shift of face-to-face pedagogy to emergency remote teaching mode. In that transition, teachers often do not have enough space and time to explore various technology to support their teaching and learning practices that should be done flexibly in multiple places and times. In response, the primary purposes of this article are to introduce a technology tool called Screencast-O-Matic (SOM), its potentials, and possible practices of using SOM that EFL lecturers might adopt for their teaching and learning purposes, specifically in the current pandemic era. Some of the practices discussed in this paper are the use of SOM to: record a video lecturer on how to write a paper following an APA format, give video-based feedback to students’ work, make a digital video presentation, and be a digital mirror that helps students review their speaking performance before they do an actual video presentation. The discussions of the paper are supported by some of the authors’ actual experiences in using SOM in their classrooms, related research findings, and literature. Ideas for future research are presented.